2013
DOI: 10.1371/journal.pone.0067740
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for Resistance to Sclerotinia Stem Rot and BnaC.IGMT5.a as a Candidate Gene of the Major Resistant QTL SRC6 in Brassica napus

Abstract: Stem rot caused by Sclerotinia sclerotiorum in many important dicotyledonous crops, including oilseed rape (Brassica napus), is one of the most devastating fungal diseases and imposes huge yield loss each year worldwide. Currently, breeding for Sclerotinia resistance in B. napus, as in other crops, can only rely on germplasms with quantitative resistance genes. Thus, the identification of quantitative trait locus (QTL) for S. sclerotiorum resistance/tolerance in this crop holds immediate promise for the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(154 citation statements)
references
References 47 publications
13
141
0
Order By: Relevance
“…In the field, two inoculation procedures of leaves and stems were carried out on both genotypes (90 days old) as described in detail previously [5], with some minor modifications to assess the resistance to the pathogen. The lesion length along the leaves was measured at 1, 2, 4, 6, 8 and 10 dpi, and the lesion length along the stems of both genotypes was measured at 1, 2, 4, 6, 8, 10 and 30 dpi.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field, two inoculation procedures of leaves and stems were carried out on both genotypes (90 days old) as described in detail previously [5], with some minor modifications to assess the resistance to the pathogen. The lesion length along the leaves was measured at 1, 2, 4, 6, 8 and 10 dpi, and the lesion length along the stems of both genotypes was measured at 1, 2, 4, 6, 8, 10 and 30 dpi.…”
Section: Methodsmentioning
confidence: 99%
“…SSR is reported from most of the oilseed-producing areas of the world, including China, India, Iran, USA, Brazil, Canada, Germany, Italy, Sweden, France, Finland, England and Denmark [1–4]. Sclerotinia sclerotiorum causes 0–20% of yield loss every year in Brassica napus crops and can reach up to 80% in severely infected fields in China [5]. …”
Section: Introductionmentioning
confidence: 99%
“… Based on comparative analysis by Li et al . (2015a), the independently discovered QTLs Sll16 (Zhao et al ., ) and SRC6 (Wu et al ., ) overlap, as do the independently discovered QTLs LRA9, SRA9 (Wu et al ., ) and qSR11‐1 (Wei et al ., ). …”
Section: Genetic Resistancementioning
confidence: 97%
“…For many of the mapping studies, resistance was assayed at multiple B. napus life stages. Studies that assayed both seedling and mature plant life stages often found QTLs that were specific to each life stage (Zhao & Meng, ; Wu et al ., ). Notably, Wu et al .…”
Section: Genetic Resistancementioning
confidence: 99%
“…Detached leaf assays have been used to identify quantitative trait loci for resistance to S. sclerotiorum in soybean (Arahana et al, 2001) and Brassica napus (Wu et al, 2013). In peanut, Hollowell et al (2003) developed an excised leaflet assay after obtaining inconsistent results using detached stems.…”
mentioning
confidence: 99%